ECO FAMILY : METODE PARENTING ANAK USIA DINI UNTUK MEMBENTUK GENERASI LITERASI LINGKUNGAN - Wisnu Budi Wijaya, I Komang (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2019)
According to Hinduism, humans achieve happiness through several methods, one of them is to maintain the harmony with environment. Humans and the environment are two subjects who demand each other. Human life depends on the state of plants and the preservation of plants by humans. However, the fact is, decaying of environment is getting worse and, ironically, humans are the main actors of the damage. Therefore, it is necessary to establish a generation with environment literacy to maintain environment stability. The formation of environment literacy spirit should start from early childhood. The role of the family to form children with environment literacy is enormous. In order to build spirit of environment literacy optimally, it is necessary to have a conception of environmental design on family: Eco-family. Eco-family is a family concept that has an environment caring attitude which is manifested in daily actions. Planting the value of environment literacy on early childhood through the concept of Eco-family takes precedence on the dimensions of attitude.Keywords: literacy, environment, children, eco-family